Cerebellar structural and functional abnormalities in first-episode and drug-naive patients with schizophrenia: A meta-analysis. (30th January 2019) - Ding, Yudan; Ou, Yangpan; Pan, Pan; Shan, Xiaoxiao; Chen, Jindong; Liu, Feng; Zhao, Jingping; Guo, Wenbin
Highlights: Patients with schizophrenia and 704 healthy controls were involved in this meta-analysis. Patients showed cerebellar abnormalities with the movement and affective-cognitive networks. Significant discrepancies were found between patients with different clinical characteristics. Abstract: Schizophrenia (SZ) is a mental disorder that involves cerebral and cerebellar abnormalities. The cerebellum plays an indispensable role in the pathophysiology of SZ. However, individual studies pertaining to the structural and resting-state functional cerebellar abnormalities in patients with SZ have been inconsistent. To make a relatively robust conclusion with little interference, such as different disease episode times and antipsychotic treatment, we conducted this meta-analysis as a first attempt to comprehensively analyze and combine studies of voxel-based morphometry (VBM), amplitude of low-frequency fluctuation (ALFF), and functional connectivity strength (FCS) in first-episode and drug-naive SZ patients, employing the Seed-based d Mapping (SDM) method. Thirteen VBM studies, eight ALFF studies, and three FCS studies involving 783 patients and 704 matched healthy controls were included. Our results showed the presence of structural and functional abnormalities within the cerebellar regions, including most superior/anterior cerebellum (lobule III-V or VI) and posterior/inferior cerebellum (lobule VIII) related to motor function, and posterior cerebellum (lobule VIIa, Crus I, and II) associated with cognition and emotion, and such anomalies might be related to illness duration and clinical symptom severity.